To Speed Our Boys Home... Produce and Conserve. Share and Play Square. Home Front Propaganda and Food during World War II: Rewriting Gender? - Hélène Le Dantec-Lowry (Transatlantica)
This article examines propaganda targeting American women during World War II, especially the numerous messages linked to the home and cooking. It shows that the posters and booklets issued by the federal government, along with advertising and cookbooks, constructed a very narrow class, gender, and ethnoracial vision that confined women to their home, even when some of them were encouraged to replace men in industrial jobs. This construction had two concomitant consequences: first, the focus on 1950s white suburban housewives in middle-class suburbs during the Cold war, and second, the creation of female solidarity, which, in part, led to feminist demands in the 1960s.